Biomotor systems in elite junior judoists - Krstulovic, S.; Zuvela, F.; Katic, R. (Collegium Antropologicum, 2006)
The aim of the study was to assess the impact of motor abilities and morphological characteristics on junior judoka performance. A set of 14 morphological parameters and a set of 14 motor tests as predictor variables, and 3 variables evaluating judo performance as criteria were applied in a sample of 40 judoists aged 17 years 6 months. Three factors were isolated by factor analysis in morphological area: factor of muscle mass and bone volume (muscle and bone mass - mesoectomorphy), factor of longitudinal skeleton dimensionality, and factor of subcutaneous adipose tissue (endomorphy). Four factors were isolated by factor analysis in motor area: factor of coordination and strength (regulated force), factor of movement frequency (speed), factor of muscular and cardiovascular endurance (endurance), and factor of tonus regulation and synergy regulation (flexibility/balance). Canonical correlation analysis between latent morphological and motor variables, and variables for assessment of competitive performance of junior judoists yielded two linear combinations, i.e. two pairs of canonical factors. Correlation in the first pair of canonical factors was underlain by the favorable impact of coordination/strength, speed, flexibility and balance, along with above-average muscle mass and bone volume, and above-average skeleton longitudinality on performance in judo. Correlation in the second pair of canonical factors was based on positive determination of above-average endurance along with moderate coordination/strength and speed, and below-average muscle mass and bone volume and skeleton longitudinality upon judo performance as expressed by the fight winning score.